1998
DOI: 10.1097/00000539-199807000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Medial Canthus Single-Injection Episcleral (Sub-Tenon Anesthesia)

Abstract: We describe medial canthus single-injection periocular anesthesia by a computed tomography injection study in eight human cadaver eyes. It was confirmed to be an episcleral injection. Akinesia of the eyeball is provided by spreading of the local anesthetic solution from the episcleral space to the rectus muscle sheaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
1
22
0
3
Order By: Relevance
“…A punção periconal, igualmente às outras técnicas, tem mostrado bons resultados quanto à instalação rápida e qualidade do bloqueio. O ponto de acesso na região caruncular ou canto medial é uma boa alternativa para o bloqueio peribulbar, mesmo como punção única [15][16][17][18] . Ripart e col., utilizando punção única na região caruncular, denominaram a técnica como injeção episcleral ou sub-capsular de Tenon, realizada lateralmente à carúncula na região semilunar da conjuntiva 19 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A punção periconal, igualmente às outras técnicas, tem mostrado bons resultados quanto à instalação rápida e qualidade do bloqueio. O ponto de acesso na região caruncular ou canto medial é uma boa alternativa para o bloqueio peribulbar, mesmo como punção única [15][16][17][18] . Ripart e col., utilizando punção única na região caruncular, denominaram a técnica como injeção episcleral ou sub-capsular de Tenon, realizada lateralmente à carúncula na região semilunar da conjuntiva 19 .…”
Section: Discussionunclassified
“…Periconal puncture, as other techniques, has shown to be effective in terms of fast onset and blockade quality. The access site at the medial canthus is a good peribulbar blockade alternative, even as a single puncture [15][16][17][18] . Ripart et al, using a single medial canthus puncture, have named the technique episcleral or sub-Tenon injection, performed laterally to the caruncle at the semilunar region of the conjunctiva 19 .…”
Section: M15mentioning
confidence: 99%
“…Niemi-Murola et al 28 and Stevens and Restori 29 found that with sub-Tenon's injection, the liquid accumulated in the anterior part of the orbit and later diffused into the back part of the orbital facial sheath of the eyeball, with good continuity between the posterior Tenon's capsule and the Propofol sedation with sub-Tenon's infusion M Snir et al retrobulbar and muscle cone space. Ripat et al 12,13,30 found sub-Tenon's anaesthesia to be precise and longlasting, even when small volumes were used. Our method has several unique aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Standard texts suggest between 3 and 5 ml for sub-Tenon's injection but do not enlarge on when to use this range of volumes [2,4]. Ripart [5] states that 4 ml is sufficient to surround the globe and provide akinesia with a sub-Tenon's medial canthus injection. Finally, in Guise's prospective study of 6000 blocks [3], the average injectate for all sub-Tenon's injections is 3.8 ml (range 3-8 ml).…”
mentioning
confidence: 99%
“…The patient's background is an important consideration as the Asian orbit is shallower than the Caucasian orbit, (on average 48.3 mm vs 50.0 mm deep) which produces the smaller orbital volume [1]. We know from Ripart's study, on eight cadaveric eyes, that 4 ml of radio opaque dye completely fills the sub-Tenon's space on CT scanning, and that any volume above 4 ml overflows the subTenon's space [5]. In terms of the pressure effects, Riemann et al [6] found that 5 ml of retrobulbar local anaesthetic increases tissue tension in the orbit from 4.4 (SD 2.2) mmHg pre-injection to 12.0 (SD 3.6) mmHg, declining to 6.7 (2.2) mmHg after 5 min.…”
mentioning
confidence: 99%